Faktor-Faktor Yang Mempengaruhi Financial Performance Pada Perusahaan Manufaktur Di BEI - Felicia Suryanto, Lukman Surjadi (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to obtain empirical evidence about the effects of financial leverage, firm size, and dividend policy on financial performance in manufacturing industries listed in Indonesian Stock Exchange in 2016-2018. This research used 40 samples of manufacturing companies that have been previously selected using purposive sampling method. Secondary data was used in the form of financial statements and annual reports. This research data was processed using EViews 11. The result of this research shows that financial leverage and dividend policy have a significant effect on financial performance, while firm size does not has a significant effect on financial performance. Suggestions for the next study is to add another independent variables to strengthen the ability of independent variables in explaining the dependent variable, such as intellectual capital, company age, and liquidity.